Advanced drying technologies - Kudra, Tadeusz (Macrel Dekker, Inc., 2002)
Presents the most recent breakthroughs in thermal dehydration, drying, and dewatering. Emphasizes emerging equipment, innovative techniques, and cost-effective strategies for a variety of industrial and agricultural applications.